DIGITAL INTELLIGENCE: CONSUMPTIVE BEHAVIOR REDUCTION EFFORTS GLOBAL SOCIETY AGAINST HOAX INFORMATION - Eka Wulandari, Iis (QAULAN: Journal of Islamic Communication, 2021)
The development of information technology contributes to creating media diversity. This rapid development has triggered a shift in the availability of access from limited access to abundant media. The birth of cyber media is one sign of this diversity. However, not everything that develops has a positive impact, but many audiences complain about the reality that has entered the era of a world crowded with media. The existence of this phenomenon gives rise to freedom in the creation and dissemination of information which leads to the delivery of irresponsible messages. So that the phenomenon of the spread of fake news or hoaxes is increasing significantly in Indonesia and even in the world. Unfortunately, most netizens who take part in this new media era do not pay attention to cyber media law and ethics. In addition, they also lack knowledge about what, why and how media literacy is applied. From the emergence of this problem, it is important for netizens and audiences to know the importance of digital intelligence, as an effort to reduce the consumptive behavior of the global community in consuming information from hoax crimes.. Keywords: Cyber Media, Hoax, Digital Intelligence